A Business Analysis of the Partial Nationalization of Zambia's Copper Industry, 1969–1981 - Stoever, William A. (Journal of International Business Studies, 1985)
The Zambian government's 51% nationalization of the country's copper mines in 1969 was motivated partly for economic purposes—a kind of learning-by-doing was anticipated—and partly for political reasons. It appears that the Zambians did obtain a semblance of managerial control and “national ownership,” but at a very high financial price. The article estimates that the direct revenue loss was over $1 billion through 1981, not counting various disguised costs. The findings are based primarily on an in-depth analysis of the mining companies' annual reports from 1964 through 1981.